Synthesis and Characterisation of Nano Zero-Valent Iron for the Reduction and Immobilisation of Cr(VI) in Water Resources - Martin Stojchevski; Stefan Kuvendziev; Zoran Bozinovski; Petre Makreski; Perica Paunović; Mirko Marinkovski; Kiril Lisichkov (Kemija u Industriji)
Nano zero-valent iron (nZVI) was synthesised through the chemical reduction of Fe(III) ions using iron(III) chloride and sodium borohydride solutions under atmospheric conditions. Structural and chemical characterisation of nZVI was performed using scanning electron microscopy (SEM), X-ray powder diffraction (XRPD), energy dispersive X-ray fluorescence spectrometry (EDXRF), thermogravimetric/differential thermal analysis (TGA/DTA), specific surface area analysis (SSA), and ultraviolet-visible spectroscopy (UV/Vis). The synthesised iron exhibited a zero oxidation state and a nearly one-dimensional morphology. The zero-valent iron nanoparticles with a body-centred cubic crystal structure remained chemically stable for several months. The mean diameter of individual nanoparticles was less than 60 nm, with an SSA of 23.79 m2 g–1. The synthesised nZVI was applied for the catalytic reduction of Cr(VI) in an aqueous solution. The effects of contact time and initial nZVI concentration on the efficiency of Cr(VI) removal from aqueous solution were investigated. The removal efficiency reached 44.2, 74.6, and 94.5 % after 300 min at initial nZVI concentrations of 20, 40, and 60 mg l–1, respectively. This study suggests that the obtained nZVI is an environmentally friendly and effective reducing agent for treating wastewater and groundwater contaminated with hexavalent chromium.